2020
DOI: 10.3390/su12198036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perceived Site Qualities and Experiences of Urban Public Spaces: A Case Study of Social Media Reviews in Bryant Park, New York City

Abstract: Urban public spaces are a key component to the well-being and prosperity of modern society. It has been increasingly important to improve the qualities and maximize the usages of urban public spaces. There is a lack of studies that investigate how people use and perceive urban parks using quantitative analysis of location-based social media reviews. This study tackles this gap by introducing a case study that uses social media reviews (Tripadivisor.com) to understand the perceived site quality and experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…From the review, we identified a number of advantages and limitations of using social media data for urban park studies. The advantages included the availability of a very large amount of data that cannot be obtained through traditional methods such as surveys, and the possibility of receiving more "honest" answers [52]. The potential limitations identified include respondent bias, data security issues, and others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the review, we identified a number of advantages and limitations of using social media data for urban park studies. The advantages included the availability of a very large amount of data that cannot be obtained through traditional methods such as surveys, and the possibility of receiving more "honest" answers [52]. The potential limitations identified include respondent bias, data security issues, and others.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the number of park visitors increases in April, May, June and October [50,53,56,58], while in Europe, both late spring (from May onwards) and the summer months show the highest number of park visitors [18,43]. May, June, September, and October [25] and, in New York, December, which apparently shows an increase [52], are the peak months in North America. However, worldwide, visits to urban green spaces are mainly popular on weekends and on public holidays [18,43,50,53,58].…”
Section: Main Aims and Findings Of Studies Using Social Media Data To...mentioning
confidence: 98%
See 3 more Smart Citations